Extremely Strong, Non-ionic Bases: Syntheses and Applications - Reinhard Schwesinger (CHIMIA)
Monomeric and polymeric peralkylated triamino(imino)phosphoranes have been synthesized from inexpensive starting materials. The monomers are inert, distillable liquids that exhibit a basicity of up to 10000 times the basicity of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU). Applications in organic synthesis are presented, advantages over common bases discussed.